Myopericardial Diseases Diagnosis and Management - Imazio, Massimo (Springer International Publishing : Imprint: Springer, 2016)
This book reviews current knowledge and recent advances in the diagnosis and management of myopericardial diseases, a spectrum of medical diseases and syndromes affecting a significant proportion of patients in clinical practice and presenting either as an isolated process or as a manifestation of a systemic disease. Unlike in other books, both pericardial and myocardial diseases are fully covered. Detailed guidance is provided on diagnosis and the role of integrated cardiovascular imaging, medical therapy, interventional diagnosis and therapy, and surgical diagnosis and therapy. Importantly, up-to-date original information is presented on indications and guidelines/recommendations planned for publication in 2015. This well-illustrated book will be an invaluable aid to diagnosis and management for practitioners in a range of medical specialties, including cardiology, internal medicine, rheumatology, family medicine, cardiac surgery, nephrology, and endocrinology.